2018
DOI: 10.3390/su10051671
|View full text |Cite
|
Sign up to set email alerts
|

Lighting Design for Energy Sustainability, Information, and Perception. A Museum Environment as a Case Study

Abstract: Abstract:The aim of our research is to investigate the physical connection between light, perception, and information by means of an integrated methodological approach. The proposed method was used for sustainable lighting design aiming at light efficacy and quality, visual perception, communication, and energy saving. Three types of synergic measurement were carried out: photometric, colourimetric, and perception measurements. Starting from the results and the post-processing of photometric and colourimetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Although the PDS method has been utilised in product design for many years, the incorporation of ecoconstrains in the PDS has not been given enough attention, such as those [14][15][16][17] cited in the PDS literature review given in the introduction section. The existing research found in the literature, such as those [18][19][20][21] reviewed in the introduction section, focuses in particular on some aspects of the environmental impact of the lighting products, such as energy consumption, eco-efficiency, eco-cost and LCA. None of them considered the full list of eco-PDS.…”
Section: Eco-design Aims With Related Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PDS method has been utilised in product design for many years, the incorporation of ecoconstrains in the PDS has not been given enough attention, such as those [14][15][16][17] cited in the PDS literature review given in the introduction section. The existing research found in the literature, such as those [18][19][20][21] reviewed in the introduction section, focuses in particular on some aspects of the environmental impact of the lighting products, such as energy consumption, eco-efficiency, eco-cost and LCA. None of them considered the full list of eco-PDS.…”
Section: Eco-design Aims With Related Issuesmentioning
confidence: 99%
“…For example, Zehra, Korkmaz and Ahmeda [18] conducted research in sustainable lighting systems for university buildings. Balocco and Volante [19] considered a museum environment as a case study to implement a lighting design system to reduce energy consumption, whilst enhancing information and perception. Klaassen,et al [20] investigated the eco-efficient value creation of residential street lighting systems by simultaneously analysing the value, costs and eco-costs during the design and engineering phase.…”
Section: Introductionmentioning
confidence: 99%
“…In these circumstances, it is assumed that the indoor lighting system is used in VLC, and so perturbations from artificial lighting are not implicated. So, the high SNR indoor conditions enable the usage of the VLC technology in high data rate applications, coined today as Li-Fi technology [26,27], high precision indoor location [28][29][30], Internet of Things (IoT) services [31], location based informational systems [32], smartphone applications [33], and future 5G/6G technologies [26,34]. On the other hand, outdoor applications are affected by numerous sources of artificial light.…”
Section: Optical Interferences Associated Issues and Solutionsmentioning
confidence: 99%
“…However, it does have consequences in terms of the rational use of energy (optimal combination of natural and artificial light and their control), energy saving, environmental and light quality sustainability for correct vision and perception, as well as comfort, health and safety. The same is true of the HVAC plant project [19,20]: energy refurbishment and retrofitting of a plant system have major consequences for the rational use of energy, energy saving, efficient solutions for indoor air quality, as well as thermal comfort, health and safety.However, the sustainability of a lighting design should be conceived in its ability to carry information: light is an information channel that carries signals with informational and cultural content [21].Our research grew from an ample strategic project of the University of Florence: "Preliminary technical and economic feasibility projects on University of Florence strategic interventions, inside an experimental laboratory". Sustainability 2019, 11, 3145 3 of 17The aim of our research is therefore to evaluate how a sustainable lighting project can emphasize the historical, cultural and social value of buildings, as well as allow the recovery of their high historical, artistic and interpretive value.…”
mentioning
confidence: 99%
“…However, the sustainability of a lighting design should be conceived in its ability to carry information: light is an information channel that carries signals with informational and cultural content [21].…”
mentioning
confidence: 99%